The Russian Council of Experts for Use of the Innovative Anabolic Agent Forsteo®(Teriparatide) in the Treatment of Severe Osteoporosis - Olga Mikhailovna Lesnyak (Современная ревматология)
The meeting of the Russian Council of Experts for the use of the novel anabolic agent Forsteo®(teriparatide) to treat osteoporosis (OP) was held in Moscow on June 29, 2013. The meeting was attended by leading Russian OP specialists, including the members of the Russian Osteoporosis Association and its Presidium.  The participants of the Council of Experts noted the great social importance of severe OP, which was associated primarily with its consequences, such as fractures causing an increase in disability and mortality rates in elderly people, and discussed the possibilities and benefits of the new approach to treating OP with teriparatide, the first drug permitting the formation of new bone tissue. The experts have recommended teriparatide for use within the registered indications in the following groups of patients: those who have severe OP (≥1 vertebral fractures, hip fracture of vertebral bodies or a fracture of the proximal femur, multiple recurrent fractures of skeletal bones) as first-line therapy; those who had ineffective previous antiosteoporotic therapy (new fractures occurring during the treatment and/or a continuing decline in bone mineral density), those who are intolerant to other medications for OP, or who have contraindications to their use.